2008
DOI: 10.1596/1813-9450-4704
|View full text |Cite
|
Sign up to set email alerts
|

Gender And Asset Ownership: A Guide To Collecting Individual-Level Data

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
(46 reference statements)
1
55
0
2
Order By: Relevance
“…As suggested by Doss et al (2007), gross assets are calculated from six categories: land owned, livestock wealth, dwelling and ponds, productive assets, physical assets and financial assets (including savings and lending). Household income includes income from agriculture, poultry and livestock, wages, fisheries and forest resources, rent, remittances, and enterprise.…”
Section: Datamentioning
confidence: 99%
“…As suggested by Doss et al (2007), gross assets are calculated from six categories: land owned, livestock wealth, dwelling and ponds, productive assets, physical assets and financial assets (including savings and lending). Household income includes income from agriculture, poultry and livestock, wages, fisheries and forest resources, rent, remittances, and enterprise.…”
Section: Datamentioning
confidence: 99%
“…In addition, research on gender differences in human capital since the 1990s has repeatedly shown that gender inequality in education reduces national per capita income growth ( These and other studies make a convincing case that closing the gap between men's and women's ownership of assets is not only important for women's empowerment and well-being but is also a necessary step towards achieving global development goals. As explained by Doss, Grown, and Deere (2008: 3):…”
mentioning
confidence: 92%
“…In this case, women's rights to land may be either use rights or permanent rights. In Latin America women become landowners mainly through inheritance while men are much more likely to acquire land through purchases in land markets (Doss et al 2008). There are also varying levels of knowledge on the gendered patterns of asset ownership with relatively more knowledge surrounding physical and tangible assets and education compared to other nontangible assets.…”
mentioning
confidence: 99%
“…First, achievement of a more equitable gendered distribution of assets is an important development goal. Second, ownership of assets is not only a measure of opportunities (through the ability to generate income or additional wealth) or outcomes (net wealth), it is critically important to women's bargaining power and hence their economic empowerment (Doss et al, 2008). Increasing women's access to assets and narrowing the gender-asset gap would directly improve women's wellbeing by reducing their vulnerability and lead to better development outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, having access to land helps with access to credit, which helps with access to purchased inputs (FAO, 2011). Further, women's ability to accumulate wealth is conditioned by the state, family, community and the market (Deere and Doss, 2006a;Doss et al, 2008). Historically, state laws limited women's ownership of assets, but reforms in such legislations have facilitated women's accumulation of wealth.…”
Section: Introductionmentioning
confidence: 99%